The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1073/pnas.0702955104
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of chemotherapy resistance of mammary tumors in a conditional mouse model for hereditary breast cancer

Abstract: We have studied in vivo responses of ''spontaneous'' Brca1-and p53-deficient mammary tumors arising in conditional mouse mutants to treatment with doxorubicin, docetaxel, or cisplatin. Like human tumors, the response of individual mouse tumors varies, but eventually they all become resistant to the maximum tolerable dose of doxorubicin or docetaxel. The tumors also respond well to cisplatin but do not become resistant, even after multiple treatments in which tumors appear to regrow from a small fraction of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
261
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(277 citation statements)
references
References 47 publications
16
261
0
Order By: Relevance
“…In some settings efflux pump overexpression may predominate (35), whereas in other settings, blocked apoptosis or senescence may be largely responsible for resistance (18,36). Our studies using RNAi in vivo, together with our observation that relapsed tumors frequently display altered topoisomerase levels compared with the parental tumor, suggest that topoisomerase expression levels are relevant determinants of therapeutic response.…”
Section: Discussionmentioning
confidence: 69%
“…In some settings efflux pump overexpression may predominate (35), whereas in other settings, blocked apoptosis or senescence may be largely responsible for resistance (18,36). Our studies using RNAi in vivo, together with our observation that relapsed tumors frequently display altered topoisomerase levels compared with the parental tumor, suggest that topoisomerase expression levels are relevant determinants of therapeutic response.…”
Section: Discussionmentioning
confidence: 69%
“…This observation suggested that ICL might be utilized as targeted therapy for BRCA1-mutant breast and ovarian cancers. Breast cancers that arose in mice engineered to have tissue-specific knockout of Brca1 and p53 are exquisitely sensitive to treatment with platinum compounds (Rottenberg et al, 2007). Moreover, these BRCA1 2/2 tumors did not develop resistance to despite repeated treatments and late recurrences remained platinum sensitive (Rottenberg et al, 2007).…”
Section: Brca1 and Dna Repairmentioning
confidence: 99%
“…With regard to this time issue, conditional Brca1 mouse models that develop mammary tumours with strong resemblance to human BRCA1-mutated breast tumours McCarthy et al, 2007) can be very helpful in predicting response and resistance to conventional and targeted therapeutics. Our K14cre;Brca1 F5 -13/F5 -13 ;Trp53 F2 -10/F 2 -10 mouse model was used for studying responses to various conventional chemotherapeutics, such as doxorubicin, docetaxel and cisplatin, and for analysing the mechanisms of acquired resistance (Rottenberg et al, 2007). Similar to the human situation, heterogeneity in the response of individual mouse mammary tumours was observed, but eventually all tumours became resistant to doxorubicin and docetaxel.…”
Section: Chemotherapeutic Interventions In Brca1 Modelsmentioning
confidence: 99%
“…This rapid recurrence could suggest the existence of a population of platinum-resistant cells that are selected during a second round of platinum treatment. An important difference between the two studies described above is that Rottenberg et al (2007) used a mouse model with a conditional Brca1 null allele, whereas Shafee et al (2008) used a Brca1 hypomorphic allele that still expresses the Brca1-D11 isoform after Cre-mediated deletion of exon 11. Furthermore, the platinum treatment regime differs considerably between the two studies.…”
Section: Chemotherapeutic Interventions In Brca1 Modelsmentioning
confidence: 99%
See 1 more Smart Citation